Heterologous hyperimmune polyclonal antibodies against SARS-COV-2: A broad coverage, affordable, and scalable potential immunotherapy for Covid-19 - Alape Girón, Alberto (2021)
The emergence and dissemination of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and the resulting COVID-19 pandemic triggered a global public health crisis. Although several SARS-CoV-2 vaccines have been developed, demand far exceeds supply, access to them is inequitable, and thus, populations in low- and middle-income countries are unlikely to be protected soon (1). Furthermore, there are no specific therapies available, which is a challenge for COVID-19 patient care (2). Thus, the appearance of SARS-CoV-2 variants and reports of reinfections associated with immune escape (3, 4) highlight the urgent need for effective and broad coverage COVID-19 therapeutics. Intravenous administration of human or heterologous antibodies is a therapy successfully used in patients with viral respiratory diseases (5). Accordingly, formulations containing SARS-CoV-2 specific antibodies are an attractive therapeutic option for COVID-19 patients (6). SARS-CoV-2 specific antibodies could limit infection by direct virion neutralization and/or by targeting infected cells for elimination via complement or antibody-mediated cytotoxicity (6). Specific SARS-CoV-2 antibody-based therapeutics include convalescent plasma (CP), monoclonal antibodies (mAbs), human polyclonal IgG formulations purified from CP or transgenic animals, and heterologous hyperimmune polyclonal antibodies (pAbs) (6). Although the window for using antibody-based therapeutics varies, clinical data show that they are mainly effective if administered early after symptoms onset (6).